Group rumination-focused cognitive-behavioural therapy (CBT) v. group CBT for depression: phase II trial. Issue 1 (11th January 2019) - Hvenegaard, Morten; Moeller, Stine B.; Poulsen, Stig; Gondan, Matthias; Grafton, Ben; Austin, Stephen F.; Kistrup, Morten; Rosenberg, Nicole G. K.; Howard, Henriette; Watkins, Edward R.
Abstract: Background: Although cognitive-behavioural therapy (CBT) is an effective treatment for depression, less than half of patients achieve satisfactory symptom reduction during treatment. Targeting known psychopathological processes such as rumination may increase treatment efficacy. The aim of this study was to test whether adding group rumination-focused CBT (RFCBT) that explicitly targets rumination to routine medical management is superior to adding group CBT to routine medical management in treating major depression. Methods: A total of 131 outpatients with major depression were randomly allocated to 12 sessions group RFCBT v. group CBT, each in addition to routine medical management. The primary outcome was observer-rated symptoms of depression at the end of treatment measured on the Hamilton Rating Scale for Depression. Secondary outcomes were rumination at post-treatment and depressive symptoms at 6 months follow-up (Trial registered: NCT02278224). Results: RFCBT significantly improved observer-rated depressive symptoms (Cohen's d 0.38; 95% CI 0.03–0.73) relative to group CBT at post-treatment on the primary outcome. No post-treatment differences were found in rumination or in depressive symptoms at 6 months follow-up, although these secondary analyses may have been underpowered. Conclusions: This is the first randomized controlled trial providing evidence of benefits of RFCBT in major depression compared with CBT. Group RFCBT may be a beneficial alternative to group CBT for major depression.